Effects of variable versus nonvariable controlled mechanical ventilation on pulmonary inflammation in experimental acute respiratory distress syndrome in pigs. (April 2020) - Wittenstein, Jakob; Scharffenberg, Martin; Braune, Anja; Huhle, Robert; Bluth, Thomas; Herzog, Moritz; Güldner, Andreas; Ball, Lorenzo; Simonassi, Francesca; Zeidler-Rentzsch, Ines; Vidal Melo, Marcos F.; Koch, Thea; et al.
Abstract: Background: Mechanical ventilation with variable tidal volumes (VT ) may improve lung function and reduce ventilator-induced lung injury in experimental acute respiratory distress syndrome (ARDS). However, previous investigations were limited to less than 6 h, and control groups did not follow clinical standards. We hypothesised that 24 h of mechanical ventilation with variable VT reduces pulmonary inflammation (as reflected by neutrophil infiltration), compared with standard protective, nonvariable ventilation. Methods: Experimental ARDS was induced in 14 anaesthetised pigs with saline lung lavage followed by injurious mechanical ventilation. Pigs ( n =7 per group) were randomly assigned to using variable VT or nonvariable VT modes of mechanical ventilation for 24 h. In both groups, ventilator settings including positive end-expiratory pressure and oxygen inspiratory fraction were adjusted according to the ARDS Network protocol. Pulmonary inflammation (primary endpoint) and perfusion were assessed by positron emission tomography using 2-deoxy-2-[ 18 F]fluoro-d -glucose and 68 Gallium ( 68 Ga)-labelled microspheres, respectively. Gas exchange, respiratory mechanics, and haemodynamics were quantified. Lung aeration was determined using CT. Results: The specific global uptake rate of 18 F-FDG increased to a similar extent regardless of mode of mechanical ventilation (median uptake for variable VT =0.016 min −1 [inter-quartile range, 0.012–0.029] compared with median uptake for nonvariable VT =0.037 min −1 [0.008–0.053]; P =0.406). Gas exchange, respiratory mechanics, haemodynamics, and lung aeration and perfusion were similar in both variable and nonvariable VT ventilatory modes. Conclusion: In a porcine model of ARDS, 24 h of mechanical ventilation with variable VT did not attenuate pulmonary inflammation compared with standard protective mechanical ventilation with nonvariable VT .